Retrospective study of disparities in regional anesthesia and discharge opioid prescriptions at a veterans affairs medical center [version 1; peer review: 2 approved] - Anna Woodbury; Xiangqin Cui; Kathryn E. Glas; Mercy A. Udoji; Oluwatoyin Thompson (F1000Research)
Background: Abundant literature acknowledges healthcare disparities exist in medicine, especially in pain management, but disparities related to peri-operative pain management in veterans undergoing total knee arthroplasties (TKA) has not been previously described. TKAs are becoming increasingly common, and evidence suggests that perioperative regional anesthesia improves post TKA outcomes. This study aimed to determine if healthcare disparities exist pertaining to the use of regional anesthesia and the prescribing of discharge opioids for TKAs in the Veterans Affairs Health Care System (VAHCS). We hypothesized that race-based disparities would be present in the use of regional anesthesia and discharge opioid prescribing at our institution. Our secondary hypothesis was that older patients would be more likely to receive regional anesthesia and lower quantities of opioids at discharge. Methods: This was a retrospective analysis of Atlanta VAHCS patients who underwent elective unilateral primary or revision TKA surgery between 2014 and 2020. A total of 653 patients were included. Multivariate logistic regression was used to model the impact of patient demographics on nerve block use and multivariate linear regression was used to model the impact of patient demographics on total oral morphine equivalents prescribed. Results:  Our results showed that Black patients were as likely to receive regional anesthesia for their TKAs (p=0.85) but did receive less opioid pain medications at discharge (p<0.001) than White patients. We also found that older patients (> 50 years old) had significantly lower odds ratio of receiving regional anesthesia and received less opioid pain medications post TKA discharge. Conclusions: Our study showed age-based disparities in regional anesthesia utilization and discharge opioid prescriptions. It also showed race-based disparities in discharge opioid prescriptions.  Our results demonstrate the need to better understand why these differences exist within this open access system and suggests solutions based on the socioecological model to diminish them.